Penerapan Starategi Marketing pada Masa Pandemi Covid-19 dan PPKM Darurat - Mardhani Syam, Andi Zulitsnayarti (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This research was conducted to determine the marketing strategies implemented and the impact felt by MSME players during the pandemic and emergency PPKM. The object of this research is MSME actors. The method used is a qualitative research method. Types based on literature reviews, with descriptive, analytical, verification and exportative approaches. The type of data collected is secondary data which comes from collecting data reported from research journals, from newspapers or from research. The data analysis technique uses a model in the form of qualitative data analysis in the form of a literature review of various literature and conclusions. From the research results above, it can be explained that this marketing strategy can be applied among the public with a delivery system and introducing various marketing products on social media. This strategy provides good prospects for increasing sales figures for MSME products that are experiencing the impact of the COVID-19 pandemic and emergency PPKM. And the impact caused by COVID-19 and emergency PPKM is the decline in marketing levels not only in large industries but also impacting micro, small and medium producers (MSMEs).